ANALISIS PERSEPSI PEDAGANG RITEL TERHADAP FENOMENA BOIKOT PRODUK PRO ISRAEL - N, Muh Ilham; Arifin, Ibrahim (Citra Media Publishing, 2024)
This research aims to determine the perceptions of retail traders in the Bumi Tamalanrea Permai housing complex regarding the boycott of Israeli products. The boycott action is a form of support for Palestine as a result of the major conflict between Palestine and Israel. The method used is a descriptive qualitative method. Data was obtained by conducting interviews with several retail traders in the Bumi Tamalanrea Permai housing complex. Data analysis in this research involves four stages, namely data collection, data simplification, data presentation, and drawing conclusions. The results of this research show that there are differences in perspectives and responses given by traders to actions or calls to boycott pro- Israel products. There are traders who support this by stopping providing products that are on the boycott list and there are also traders who continue to sell boycotted products.